MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst, preparation method and application thereof

By preparing MOF-derived Ni single-atom supported nitrogen-doped carbon catalyst in magnesium-based hydrogen storage materials, the problem of reduced reaction kinetics caused by catalyst agglomeration is solved, and the hydrogen absorption and release efficiency and catalytic activity of hydrogen storage materials are improved.

CN116212915BActive Publication Date: 2025-01-24BEIJING HYDROGEN SOURCE INTELLIGENT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211532744.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-01-24
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

The existing magnesium hydrogen storage materials are slow to absorb and release hydrogen, and the catalysts are prone to agglomeration during intense ball milling and circulation, affecting the catalytic efficiency and reaction kinetics.

Method used

Ni-MOF is prepared at room temperature by a solution method, and then mixed and calcined with melamine with high nitrogen content. Finally, the agglomerated Ni nanoparticles are washed away through an acid washing process to form a MOF-derived Ni single atom supported nitrogen-doped carbon hydrogen storage catalyst.

Benefits of technology

It improves the utilization and catalytic activity of the metal site, significantly improves the reaction dynamics of MGH2 hydrogen storage materials, and improves the stability of the catalytic site.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212915B_ABST
    Figure CN116212915B_ABST
Patent Text Reader

Abstract

The invention discloses a MOF-derived Ni single-atom-loaded nitrogen-doped carbon hydrogen storage catalyst. Ni-MOF is prepared at room temperature by a solution method, and then mixed with high-nitrogen-content melamine and calcined. Finally, agglomerated Ni nanoparticles are washed out by an acid washing process. The carbon material coating layer derived from the calcined Ni-MOF plays a buffering role, which can not only improve the conductivity of the material, but also improve the stability of the catalytic site during the catalytic reaction. The introduction of melamine can increase the nitrogen content of the carbon material, provide abundant anchoring sites for single-atom Ni and improve its chemical stability. The prepared Ni single-atom-loaded nitrogen-doped carbon catalyst improves the utilization rate and catalytic activity of the metal site, and improves the MgH 2 Reaction kinetics of hydrogen storage materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalyst preparation, and in particular relates to a MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst, and a preparation method and application thereof. Background Art

[0002] As a clean and renewable energy, hydrogen energy can provide stable, efficient and pollution-free power, and has broad application prospects in aerospace, automobile and other fields. The storage of hydrogen energy is the core issue in promoting its application. Solid material hydrogen storage has the advantages of high safety, convenient transportation and easy operation. Solid hydrogen storage materials have become a hot research topic in countries around the world.

[0003] Magnesium-based hydrogen storage materials have large hydrogen storage capacity and low cost, but the rate of hydrogen absorption and desorption is slow, and high temperature is required to accelerate hydrogen release. Common strategies to solve this problem include alloying, nano-sizing and adding catalysts. Among these strategies, adding catalysts can accelerate the hydrogen transfer process and significantly improve the kinetic properties of hydrogen storage materials. Transition metals have high electronegativity and multivalence, and are important catalysts for improving the hydrogen storage performance of MgH2. Reducing the size of catalyst materials can effectively improve their catalytic activity, but nano-sized catalysts are more likely to agglomerate during continuous and intense ball milling and circulation. The agglomeration of the catalyst will affect its catalytic efficiency and lead to a decrease in the kinetics of the de / hydrogenation reaction. It not only affects the reaction kinetics, but also reduces the utilization rate and catalytic activity of the metal sites, and reduces the reaction kinetics of the MgH2 hydrogen storage material. Summary of the invention

[0004] The purpose of the present invention is to provide a MOF-derived Ni single-atom-loaded nitrogen-doped carbon hydrogen storage catalyst, a preparation method and application thereof. First, Ni-MOF is prepared at room temperature by a solution method, then mixed with high-nitrogen-content melamine and calcined, and finally agglomerated Ni nanoparticles are washed away by an acid washing process. The carbon material coating layer derived from the calcined Ni-MOF plays a buffering role, which can not only improve the conductivity of the material, but also improve the stability of the catalytic site during the catalytic reaction. The introduction of melamine can increase the nitrogen content of the carbon material, provide abundant anchoring sites for single-atom Ni and improve its chemical stability. The prepared Ni single-atom-loaded nitrogen-doped carbon catalyst improves the utilization rate and catalytic activity of the metal site, and improves the reaction kinetics of the MgH2 hydrogen storage material.

[0005] In order to achieve the above object, the present invention adopts the following technical solution:

[0006] The preparation method of MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst comprises the following steps:

[0007] S1. N,N-dimethylformamide, ethanol and deionized water are measured in a volume ratio of 10 to 20:1:1, and then 0.01 to 0.015 times the weight of N,N-dimethylformamide is added to terephthalic acid under ultrasonic conditions to fully disperse;

[0008] S2, taking 0.008 to 0.012 times the weight of N, N-dimethylformamide nickel chloride hexahydrate, adding it to the mixed solution evenly mixed in S1, and then adding 0.05 to 0.08 times the volume of N, N-dimethylformamide triethylamine, after fully stirring, standing for a period of time at room temperature, filtering and collecting solid precipitates, washing and drying the obtained solid precipitates to obtain Ni-MOF;

[0009] S3, weighing the Ni-MOF and melamine prepared in S2 at a weight ratio of 0.5 to 1.8:8, grinding and mixing them evenly, transferring them to an argon-protected tubular furnace for calcination, keeping the temperature for a period of time, cooling them naturally to room temperature, and collecting the products;

[0010] S4. Add the product collected in S3 into a sulfuric acid solution and soak it to remove the nanoparticles and unstable sites, thereby obtaining a MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst, named Ni-NC.

[0011] Preferably, the ultrasonic condition described in S1 has an ultrasonic frequency of 30 to 60 kHz, and the dispersion time after adding terephthalic acid is 30 to 90 minutes.

[0012] Preferably, after adding triethylamine to S2, the mixture is stirred for 8 to 15 minutes, fully mixed, and then allowed to stand at room temperature for 8 to 15 hours until all the solids in the solution are precipitated.

[0013] Preferably, the solid precipitate in S2 is washed with N,N-dimethylformamide and ethanol respectively, and the washing is continued for 4 to 6 times, and the drying temperature of the solid precipitate in S2 is 60 to 100° C., and the drying time is 20 to 50 min.

[0014] Preferably, during the calcination process in S3, the temperature of the tubular furnace is increased to 900-1100° C. at a rate of 5° C. / min, and maintained for 1.5-2.5 hours after reaching the set temperature.

[0015] Preferably, the concentration of the sulfuric acid solution in S4 is 4 to 8 mol / L, and the collected product is immersed in the sulfuric acid solution for 40 to 60 hours.

[0016] The present invention also provides a MOF-derived Ni single-atom-loaded nitrogen-doped carbon hydrogen storage catalyst prepared by the above preparation method.

[0017] The present invention also provides the use of the above-mentioned MOF-derived Ni single-atom-loaded nitrogen-doped carbon hydrogen storage catalyst or the MOF-derived Ni single-atom-loaded nitrogen-doped carbon hydrogen storage catalyst prepared by the above-mentioned preparation method in the field of solid hydrogen storage.

[0018] In addition, the present invention also provides a MgH2 composite hydrogen storage material, which is prepared by the following steps:

[0019] S1. By weight: 0.5-3 parts of the MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst prepared by the above method and 6-10 parts of MgH2 are placed in a ball mill, and then ball milling beads are added;

[0020] S2. Ball milling was performed at a speed of 450 rpm for 5 h under a hydrogen pressure of 2 MPa. The material obtained after ball milling was designated as MgH2 composite hydrogen storage material, and was stored in a glove box for later use.

[0021] Optionally, the weight ratio of the MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst to the MgH2 in step S1 is 1:4.

[0022] Optionally, the ball-to-material ratio in step S1 is 40:1.

[0023] The present invention has at least the following beneficial effects:

[0024] 1. The preparation method of single-atom-loaded nitrogen-doped carbon hydrogen storage catalyst by calcination process proposed in the present invention is simple, which proves the advantages of single-atom catalysts in the field of solid-state hydrogen storage.

[0025] 2. The present invention prepares Ni-MOF at room temperature by a solution method, and then mixes and calcines it with melamine with a high nitrogen content, and finally removes the agglomerated Ni nanoparticles by an acid washing process. The carbon material coating layer derived after the Ni-MOF is calcined plays a buffering role, which can not only improve the conductivity of the material, but also improve the stability of the catalytic site during the catalytic reaction. The introduction of melamine can increase the nitrogen content of the carbon material, provide abundant anchoring sites for single-atom Ni and improve its chemical stability. The prepared Ni single-atom-loaded nitrogen-doped carbon catalyst improves the utilization rate and catalytic activity of the metal site, and improves the reaction kinetics of the MgH2 hydrogen storage material. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope photograph of the MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst of the present invention;

[0027] Figure 2 3 is the hydrogen release curve of the hydrogen storage composite material prepared in different embodiments of the present invention at 300°C;

[0028] Figure 3 A comparison diagram of dehydrogenation activation energies of hydrogen storage composite materials prepared in different embodiments of the present invention;

[0029] Figure 4 This is a test diagram of the hydrogen storage cycle stability of the MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst of the present invention. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0031] Example 1

[0032] The preparation method of MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst comprises the following steps:

[0033] (1) Preparation of Ni-MOF: 10 mL of N,N-dimethylformamide, 1 mL of ethanol and 1 mL of water were added to a 100 mL beaker, and then 0.095 g of terephthalic acid was added under ultrasonic conditions at a frequency of 30 kHz. After uniform dispersion for 30 min, 0.076 g of nickel chloride hexahydrate was added to the above mixture. 1 mL of triethylamine was added to the above mixture, and stirred for 8 min. The resulting solution was allowed to stand at room temperature for 8 h, and the solid precipitate was collected. It was then washed with N,N-dimethylformamide and ethanol for 5 times respectively, placed in a Petri dish and dried in an oven set at 60 °C to finally obtain the product Ni-MOF.

[0034] (2) Preparation of Ni single atom-loaded nitrogen-doped carbon: Weigh 10 mg of the Ni-MOF prepared above and 160 mg of melamine, mix them in a mortar, and grind them thoroughly to make the mixture uniform; transfer the resulting mixture to an argon-protected tubular furnace, increase the temperature to 900°C at a rate of 5°C / min, and keep it warm for 1.5 h. After the tubular furnace is naturally cooled to room temperature, the product is collected; the collected product is added to a 4 mol / L sulfuric acid solution and soaked for 40 h. After removing the nanoparticles and unstable sites, MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst carbon is obtained, which is named Ni-NC.

[0035] Example 2

[0036] The preparation method of MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst comprises the following steps:

[0037] (1) Preparation of Ni-MOF: 15 mL of N,N-dimethylformamide, 1 mL of ethanol and 1 mL of water were added to a 100 mL beaker, and then 0.2 g of terephthalic acid was added under ultrasonic conditions at a frequency of 50 kHz. After uniform mixing for 1 hour, 0.15 g of nickel chloride hexahydrate was added to the above mixture. 1 mL of triethylamine was added to the above mixture, and stirred for 10 minutes. The resulting solution was allowed to stand at room temperature for 10 hours, and the solid precipitate was collected. It was then washed with N,N-dimethylformamide and ethanol for 5 times respectively, placed in a petri dish and dried in an oven set at 80°C to finally obtain the product Ni-MOF.

[0038] (2) Preparation of Ni single atom-loaded nitrogen-doped carbon: Weigh 20 mg of the Ni-MOF prepared above and 150 mg of melamine, mix them in a mortar, and grind them thoroughly to make the mixture uniform; transfer the obtained mixture to an argon-protected tube furnace, increase the temperature to 1000°C at 5°C / min, and keep it warm for 2 h. After the tube furnace is naturally cooled to room temperature, the product is collected; the collected product is added to a 5 mol / L sulfuric acid solution and soaked for 48 h. After removing the nanoparticles and unstable sites, Ni single atom-loaded nitrogen-doped carbon is obtained, which is named Ni-NC.

[0039] Example 3

[0040] The preparation method of MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst comprises the following steps:

[0041] (1) Preparation of Ni-MOF: 20 mL of N,N-dimethylformamide, 1 mL of ethanol and 1 mL of water were added to a 100 mL beaker, and then 0.28 g of terephthalic acid was added under ultrasonic conditions at a frequency of 60 kHz. After uniform dispersion for 90 min, 0.23 g of nickel chloride hexahydrate was added to the above mixture. 1 mL of triethylamine was added to the above mixture, and stirred for 15 min. The resulting solution was allowed to stand at room temperature for 15 h, and the solid precipitate was collected. It was then washed with N,N-dimethylformamide and ethanol for 5 times respectively, placed in a Petri dish and dried in an oven set at 100 °C to finally obtain the product Ni-MOF.

[0042] (2) Preparation of Ni single atom-loaded nitrogen-doped carbon: Weigh 34 mg of the Ni-MOF prepared above and 150 mg of melamine, mix them in a mortar, and grind them thoroughly to make the mixture uniform; transfer the obtained mixture to an argon-protected tube furnace, increase the temperature to 1100°C at 5°C / min, and keep it warm for 2.5 hours. After the tube furnace is naturally cooled to room temperature, the product is collected; the collected product is added to 8 mol / L sulfuric acid solution and soaked for 60 hours. After removing the nanoparticles and unstable sites, MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst carbon is obtained, which is named Ni-NC.

[0043] Among Examples 1 to 3, the Ni-MOF and Ni-NC prepared by the method of Example 2 have the highest yield and more stable and uniform structure, so Example 2 is the best ratio. The MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst carbon (Ni-NC) prepared in Example 2 was taken, and the structure of Ni-NC was photographed with a scanning electron microscope. The scanning electron microscope photo is shown in FIG. Figure 1 shown.

[0044] Example 4

[0045] As described in Example 2, the sample obtained after calcination without soaking in sulfuric acid is Ni nanoparticles loaded with nitrogen-doped carbon, named NiNP-NC.

[0046] Example 5

[0047] As described in Example 2, the sample obtained by not adding nickel chloride hexahydrate during the preparation of Ni-MOF is nitrogen-doped carbon, named NC.

[0048] Example 6

[0049] 0.8 g of MgH2 and 0.2 g of the sample prepared in Example 2 were weighed and placed in a ball mill, and then 40 g of ball milling beads were added. The mixture was ball milled at a speed of 450 rpm for 5 h under a hydrogen pressure of 2 MPa to obtain MgH2+Ni-NC.

[0050] Example 7

[0051] 0.8 g of MgH2 and 0.2 g of the sample prepared in Example 4 were weighed and placed in a ball mill, and then 40 g of ball milling beads were added. The mixture was ball milled at a speed of 450 rpm for 5 h under a hydrogen pressure of 2 MPa to obtain MgH2+NiNP-NC.

[0052] Example 8

[0053] 0.8 g of MgH2 and 0.2 g of the sample prepared in Example 5 were weighed and placed in a ball mill, and then 40 g of ball milling beads were added. The mixture was ball milled at a speed of 450 rpm for 5 h under a hydrogen pressure of 2 MPa to obtain MgH2+NC.

[0054] Research on hydrogen storage performance:

[0055] At different heating rates, the hydrogen release performance of the MgH2+Ni-NC, MgH2+NiNP-NC, MgH2+NC composite materials and pure MgH2 materials prepared in the above examples at 300°C was studied by differential scanning calorimetry, and the obtained data were fitted using the Kissinger method. The fitting results are shown in Figure 2 , Figure 3 As shown, the MgH2 of the composite Ni-NC catalyst has the lowest hydrogen desorption activation energy, indicating that the catalytic effect of single atoms is superior to that of nanoparticles, and the introduction of single atoms can effectively improve the hydrogen storage kinetics of MgH2.

[0056] In addition, the hydrogen storage cycle stability of MgH2+Ni-NC was tested, and the test results are as follows: Figure 4 shown.

[0057] By adopting the above technical scheme, Ni-MOF is first prepared at room temperature by a solution method, then mixed with high-nitrogen-content melamine and calcined, and finally agglomerated Ni nanoparticles are washed away by an acid washing process. The carbon material coating layer derived after the calcination of Ni-MOF plays a buffering role, which not only improves the conductivity of the material, but also improves the stability of the catalytic site during the catalytic reaction. The introduction of melamine can increase the nitrogen content of the carbon material, provide rich anchoring sites for single-atom Ni and improve its chemical stability. The prepared Ni single-atom-loaded nitrogen-doped carbon catalyst improves the utilization rate and catalytic activity of the metal site, and improves the reaction kinetics of the MgH2 hydrogen storage material.

[0058] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. Application of MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst in the field of solid hydrogen storage, characterized in that: The preparation method of MOF-derived Ni single atom-supported nitrogen-doped carbon hydrogen storage catalyst comprises the following steps: S1. N,N-dimethylformamide, ethanol and deionized water are measured in a volume ratio of 10 to 20:1:1, and then 0.01 to 0.015 times the weight of N,N-dimethylformamide is added to terephthalic acid under ultrasonic conditions to fully disperse; S2, taking 0.008 to 0.012 times the weight of N, N-dimethylformamide nickel chloride hexahydrate, adding it to the mixed solution evenly mixed in S1, and then adding 0.05 to 0.08 times the volume of N, N-dimethylformamide triethylamine, after fully stirring, standing for a period of time at room temperature, filtering and collecting solid precipitates, washing and drying the obtained solid precipitates to obtain Ni-MOF; S3, weighing the Ni-MOF and melamine prepared in S2 at a weight ratio of 0.5 to 1.8:8, grinding and mixing them evenly, transferring them to an argon-protected tubular furnace for calcination, keeping the temperature for a period of time, cooling them naturally to room temperature, and collecting the products; S4. Add the product collected in S3 into a sulfuric acid solution and soak it to remove the nanoparticles and unstable sites, thereby obtaining a MOF-derived Ni single atom-loaded nitrogen-doped carbon hydrogen storage catalyst, named Ni-NC.

2. The use according to claim 1, characterized in that: The ultrasonic conditions described in S1 are that the ultrasonic frequency is 30 to 60 KHz, and the dispersion time after adding terephthalic acid is 30 to 90 minutes.

3. The use according to claim 1, characterized in that: After adding triethylamine to S2, stir for 8 to 15 minutes, mix thoroughly, and let stand at room temperature for 8 to 15 hours until all the solids in the solution are precipitated.

4. The use according to claim 1, characterized in that: The solid precipitate in S2 is washed with N,N-dimethylformamide and ethanol respectively, and the washing is continued for 4 to 6 times. The drying temperature of the solid precipitate in S2 is 60 to 100° C., and the drying time is 20 to 50 minutes.

5. The use according to claim 1, characterized in that: During the calcination process described in S3, the temperature of the tubular furnace is increased to 900-1100° C. at a rate of 5° C. / min, and maintained for 1.5-2.5 hours after reaching the set temperature.

6. The use according to claim 1, characterized in that: The concentration of the sulfuric acid solution in S4 is 4 to 8 mol / L, and the collected product is immersed in the sulfuric acid solution for 40 to 60 hours.

Citation Information

Patent Citations

  • Nickel metal organic framework supported nano bismuth vanadate catalyst and preparation method thereof

    CN109331885A

  • Preparation method for magnesium-based composite hydrogen storage material based on nano confinement of metal organic frameworks (MOFs) material

    CN110526208A